Uji Performansi Mesin Pengisi Bumbu Pasta Semi Otomatis untuk Bubur Pedas Instan - Suhendra; Feby Nopriandy; Winda Apriani (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
The main problem faced by the instant bubur pedas business unit is the filling of pasta seasoning in the packaging. The packaging of seasoning paste is currently done manually by putting the seasoning paste into the plastic packaging using a spoon. The weakness of the manual filling technique was that it has a small filling capacity and needs to be more practical and hygienic. Through this research, an effort was made to overcome these problems by creating a semi-automatic pasta seasoning filling system. This research aims to conduct performance tests on a semi-automatic pasta seasoning filling machine for instant bubur pedas and analyze the relationship between the rotation of the stepper motor and the mass of pasta seasoning coming out of the filling machine. The performance test carried out on the machine is in the form of an analysis of packaging time and packaging capacity. The independent variable was the number of stepper motor revolutions, ranging from 1 to 20. Based on the performance test results, the highest packaging capacity was obtained at 208 packs/hour in the treatment of stepper motor rotation one time, with the number of spices released at 3.29 grams. Increasing the mass of packaged spices requires more stepper motor revolutions, increasing the time needed for each packaging cycle. The stepper motor rotation and the mass of seasoning paste coming out of the filling machine show a consistent linear relationship with a coefficient of determination (R2) value of 0.9983. These results show that this machine can maintain the consistency of the mass of seasoning released per stepper motor rotation. Keywords: bubur pedas, filling machine, paste seasoning, performance test, semi-automatic